Primary leiomyosarcoma of the inferior vena cava. A case report and review of the literature - Wasiewicz, Janusz; Nasher, Mohsen; Murawa, Paweł; Nowakowski, Wojciech (Contemporary Oncology/Współczesna Onkologia, 1999)
Leiomyosarcoma of the Inferior Vena Cava is a rare tumor. Two hundred and eigtheen patients have been collected by an International Registry of Inferior Vena Cava up to 1997. We report a case of a 30-year old woman who had unexplained attacks of pain in the right-upper quadrant and radiating into the right side of the back. The tumor was widely excised. Vena Cava was sutured. The patient is alive for more than 18-months after surgery with no evidence of recurrence. Literrature is reviewed.